Visual electrophysiology and neuropsychology in bipolar disorders: A review on current state and perspectives. (September 2022) - Tursini, Katelyne; Le Cam, Steven; Schwan, Raymund; Gross, Grégory; Angioi-Duprez, Karine; Conart, Jean-Baptiste; Remy, Irving; Bernardin, Florent; Laprévote, Vincent; Knobloch, Eléa; Ricaud, Tiphaine; Rahnema, Aline; et al.
Abstract: Bipolar disorder is a lifelong condition. Today, there is a urgent need to find indicators of the disease. Specifically, they could be useful to improve the diagnosis and the early detection, the prognosis, to estimate the treatment response and to create homogeneous subgroups of patients based on similar pathophysiological mechanisms. Here, we assume that visual electrophysiology in combination with a neuropsychological assessment can give additional data to routine practice, especially to precise specific damages and pathophysiological characteristics of these patients. Visual electrophysiology is characterized by an electroretinogram and the delivery of visual evoked potentials, which measure retinal and visual cortical neuronal functioning in response to visual stimulations. This review highlights the interest of visual electrophysiology and neuropsychology performed in isolation and to present the benefits of combining these measures. We will review the results based on these measures in patients with bipolar disorders. Finally, we argue for the use of innovative techniques such as signal processing and artificial intelligence techniques for routine care and precision medicine in bipolar disorders. Highlights: Visual electrophysiology abnormalities are present in bipolar patients. The neurocognitive profile of these patients is hard to be clearly defined. Visual electrophysiology and neuropsychology are two complementary measures. Coupling these measures would be a step toward precision psychiatry. The help of artificial intelligence would help to highlight additional indicators.